Breast Neuroendocrine Tumor. Case Report and Literature Review - Lidia Torres Aja (Revista Finlay)
Primary neuroendocrine carcinomas of the breast are rare neoplasms, accounting for 2 to 5 % of breast tumors. For their diagnosis it is required that more than 50 % of the tumor present neuroendocrine features. These tumors which are observed mainly in elderly women, present as a well-defined mass, usually unaccompanied by axillary lymphadenopathy. The prognosis for this type of cancer is not enough clear yet, although recent studies show that it is similar to that of conventional infiltrating ductal carcinomas. We present the case of a 76-year-old patient who came to the clinic for having a large tumor that occupied almost all of the right breast without axillary lymphadenopathy and which was informed by paraffin biopsy as a neuroendocrine carcinoma. This is the first tumor of this histological characteristic diagnosed in Cienfuegos, reason why its publication is considered of scientific interest.